Hydrothermal synthesis and characterisation of iron cerium oxide nanoparticles for hydrogen sulphide removal application. (23rd May 2019) - To, Thien Dien; Nguyen, Huong Giang Thi; Doan, Tin Chanh Duc; Shiratori, Yusuke; Dang, Chien Mau
Iron oxide (Fe2 O3 ) is considered as an excellent catalyst for reduction of hydrogen sulphide (H2 S) due to not only good sulphur adsorption capacity but also low cost. However, the catalytic effect of Fe2 O3 is deactivated rapidly after running. Doping heteroatoms is assumed to improve its catalytic activity and extend its life time. Among doped heteroatoms, cerium doping on Fe2 O3 has exhibited an extremely high catalytic activity. In this paper, the iron cerium oxide (FeCeOx ) nanoparticles were synthesised by temperature- and time-controlled hydrothermal method. The FeCeOx nanoparticles were characterised by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), Raman spectroscopy and field emission scanning electron microscopy and energy-dispersive X-ray spectroscopy (FESEM-EDX). The results showed that the average particle size of the obtained FeCeOx was less than 40 nm and size distribution was narrow. Remarkably, the synthesised nanoscale-sized FeCeOx compound was not only highly pure but also uniform without traces of Fe2 O3 or FeOOH at 80°C for 16 h.